Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.251
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Supported Collaborative Learning in STEM Domains: Towards a Meta-synthesis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…In the mix-gender major, Table 5 shows that women in mixed-group CL classes in biology major demonstrated negative attitudes compared to single-gender classes. These findings are similar to what is resulted in nonmajor biology, which is consistent with the meta-analysis done by Hmelo-Silver (2017), where he mentioned that mixed gender grouping might affect women negatively in STEM domains [124]. Zeid and El-Bahey (2011) found that both genders' overall course performance has improved by changing the software engineering classroom composition from a mixed to a single-gender classroom in a Gulf Cooperation Council (GCC) country [125].…”
Section: Pedagogical Effect On Attitudes On Major Mix-gender Groups Learningsupporting
confidence: 90%
See 1 more Smart Citation
“…In the mix-gender major, Table 5 shows that women in mixed-group CL classes in biology major demonstrated negative attitudes compared to single-gender classes. These findings are similar to what is resulted in nonmajor biology, which is consistent with the meta-analysis done by Hmelo-Silver (2017), where he mentioned that mixed gender grouping might affect women negatively in STEM domains [124]. Zeid and El-Bahey (2011) found that both genders' overall course performance has improved by changing the software engineering classroom composition from a mixed to a single-gender classroom in a Gulf Cooperation Council (GCC) country [125].…”
Section: Pedagogical Effect On Attitudes On Major Mix-gender Groups Learningsupporting
confidence: 90%
“…the students were assessed on how worried or nervous they are when being assessed in biology. Assessing student's anxiety towards biology is essential as it is found to influence the students' grades and confidence in a subject, thereby affecting the attitude towards it [123][124][125].…”
Section: Career Motivationmentioning
confidence: 99%
“…Our assumption was that the most recent years (at the time of our study) would represent the most current thinking and a broader international research community. We did not look at what researchers did with the coding schemes and how well they addressed their research questions, as that was outside the scope of this research (Jeong et al , 2014; Jeong and Hmelo-Silver, 2015; Hmelo-Silver et al , 2017 for CSCL syntheses that address some of these questions).…”
Section: Discussionmentioning
confidence: 99%
“…Collaborative learning is considered as significant for promoting various methods of learning, especially Problem-based learning, and STEM education. Cindy has found that collaborative learning has an important role to support STEM in education (Hmelo-silver et al, 2017). Similarly, Lynch designed the robotic collaborative learning through method of STEM (Lynch, 2016).…”
Section: Stem and Collaborative Learningmentioning
confidence: 99%